2007
DOI: 10.1007/s10517-007-0335-0
|View full text |Cite
|
Sign up to set email alerts
|

Reparative reactions of the skeletal muscles in early aging OXYS rats with toxic metabolic injuries caused by bupivacaine

Abstract: Comparative analysis of reparative reactions in the anterior tibialis muscles of OXYS and Wistar rats after intramuscular injections of bupivacaine was carried out for eva, luating the regeneratory potential of skeletal muscles under conditions of chronic disorders of oxidative metabolism. Lumpy degradation of lesion foci and mononuclear cell infiltration predominated on day 1; after 3 days myoblast proliferation and fusion processes were maximally pronounced; after 7 days maturing myotubules created groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Bupivacaine is considered one of the most toxic drugs in the skeletal muscle [ 30 , 31 , 32 ], and the Burn team first discovered that local anesthetics cause changes in muscle histomorphology [ 33 ]. Gergin et al demonstrated that 0.5% bupivacaine causes the most serious damage to muscle tissue [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bupivacaine is considered one of the most toxic drugs in the skeletal muscle [ 30 , 31 , 32 ], and the Burn team first discovered that local anesthetics cause changes in muscle histomorphology [ 33 ]. Gergin et al demonstrated that 0.5% bupivacaine causes the most serious damage to muscle tissue [ 34 ].…”
Section: Discussionmentioning
confidence: 99%